BIOPHILIC DESIGN SEBAGAI PENEKANAN SPIRITUALITAS MANUSIA PADA DESAIN RUMAH RETRET KATOLIK DI KOTA BATU - James Efandaru; Heristama Anugerah Putra; Stefanus Prabani Setio Hastorahmanto (Architecture Department, Faculty of Engineering, Universitas Diponegoro, 2026)
Changing times have a complex impact on human life. Even though there are many positive influences, negative challenges such as increasing spirituality due to the pressures of modern life are also increasingly felt, resulting in spiritual forgetting. In this situation, the need for a retreat house that can offer physical and spiritual tranquility and recovery becomes very important. The research aims to design a retreat house in the city of Batu using a qualitative descriptive method approach, which focuses on in depth design principles that support mental and spiritual well-being. By adopting biophilic architectural principles, it is hoped that this design can create a harmonious relationship between humans and nature, while supporting the mental, physical and spiritual healing process. The uniqueness of this retreat house lies in the implementation of integrated biophilic elements, such as water, plants and natural lighting used in each room. Facilities are designed to encourage visitors to interact with nature, including open meditation spaces, reflection paths amidst the landscape, and prayer areas connected to the surrounding environment. The result of this research is the design of facilities that not only focus on spiritual activities, but also provide a holistic retreat experience, with an emphasis on human interaction with nature as an important aspect in the healing process